Integrating Islamic Educational Management Principles into Contemporary Bureaucratic Reform - Edi Handoko; Ismatul Izzah; Moh Abd Rahman (Al-Qalam Institue, 2026)
This study aims to analyze the implementation of Islamic educational management values as a new paradigm in bureaucratic reform within public service institutions. The research is grounded in the need to promote bureaucratic reform that not only emphasizes efficiency and effectiveness but also integrates spiritual and ethical principles derived from Islamic teachings. Employing a descriptive qualitative approach, data were collected through in-depth interviews, observations, and documentation. The findings reveal that core principles of Islamic educational management such as trustworthiness (amanah), sincerity (ikhlas), justice (adl), responsibility, and service orientation (khidmah) play a significant role in fostering a humanistic, transparent, and integrity driven work culture. The integration of these values with modern management principles contributes to improving public service quality, strengthening employees’ work ethic, and promoting a justice-oriented and community-centered bureaucracy. The study implies that Islamic educational management can serve as a sustainable policy model that harmonizes professionalism with spirituality in contemporary bureaucratic reform.